Dracula as absolute other the troubling and distracting specter of Stoker's vampire on screen - Bacon, Simon 1965- (McFarland & Company, Inc., 2019)
"This book is a study of Dracula's role of absolute Other as it appears on screen, and an investigation of popular culture's continued fascination with vampires. Drawing on vampire films spanning from the early 20th century to 2017, the author examines how different generations construct Otherness and how this is reflected in vampire media"--Page [4] of cover
Keywords: Dracula; Geschichte; Vampirfilm; Das Andere; Dracula films / History and criticism; Vampire films / History and criticism; Dracula films; Vampire films; Criticism, interpretation, etc